CRACK DETECTION USING OPERATING DEFLECTION SHAPE - Djoko Suharto; Komang Bagiasna; Zainal Abidin (Mesin, 2006)
This research presents development of vibration-based crack detection method using operating deflection shape (ODS) analysis from data measured by a Laser Doppler Vibrometer (LDV). Two types of work are conducted in this research. The first work is a numerical study, while the second work is an experimental study to verify the proposed method. In the numerical study, two types of specimen are used to simulate 2-Dimensional and 3-Dimensional problems using NASTRAN code. For the 2-Dimensional model, beams with two types of crack are tested, namely center and edge cracks. For the 3-Dimensional model, a plate specimen is tested. The length of the cracks and their locations are used as parameters to observe the ability of the proposed method to detect the existence and the location of the cracks. The results of numerical study show that the existence of cracks can be detected by using the natural frequency drops and the location of the cracks can be pinpointed by using the proposed S.Sd.D.Ms method (Square of the Second Derivative of the Deviation of the Mode Shape). In order to test the reliability of the proposed method, an experimental study is required. In this experimental study, FRF ODS measurements are conducted to derive the mode shape. Three types of specimen are measured, namely intact beam, center cracked beam, multiple center cracked beam and multiple edge cracked beam. The results of experimental study confirm that the proposed method can be used to detect the location of the cracks.